2022
DOI: 10.1097/mnm.0000000000001592
|View full text |Cite
|
Sign up to set email alerts
|

Differences in tumor-to-normal organ SUV ratios measured with 68Ga-DOTATATE PET compared with 177Lu-DOTATATE SPECT in patients with neuroendocrine tumors

Abstract: Background Our goal is to quantitatively compare radiotracer biodistributions within tumors and major normal organs on pretherapy 68 Ga-DOTATATE PET to post-therapy 177 Lu-DOTATATE single-photon emission computed tomography (SPECT) in patients receiving peptide receptor radionuclide therapy (PRRT).Methods PET/CT at ~ 60 min postinjection of Ga-68 DOTATATE and research 177 Lu-SPECT/CT imaging ~ at 4 h (SPECT1) and ~ 24 h (SPECT2) post-cycle#1 were available. Manual contours of lesions on baseline CT or MRI we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The correlation pertained to SUV ratios among the tumor, liver, and spleen. Similarly, Wong et al 45 . observed a correlation between pretherapy 68 Ga‐DOTATATE PET and posttherapy 177 Lu‐DOTATATE SPECT SUV tumor‐to‐normal organ ratios (liver, spleen, and kidneys) in 24 patients at 4 and 24 h after cycle 1.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…The correlation pertained to SUV ratios among the tumor, liver, and spleen. Similarly, Wong et al 45 . observed a correlation between pretherapy 68 Ga‐DOTATATE PET and posttherapy 177 Lu‐DOTATATE SPECT SUV tumor‐to‐normal organ ratios (liver, spleen, and kidneys) in 24 patients at 4 and 24 h after cycle 1.…”
Section: Introductionmentioning
confidence: 71%
“…The correlation pertained to SUV ratios among the tumor, liver, and spleen. Similarly, Wong et al 45 observed a correlation between pretherapy 68 Ga-DOTATATE PET and posttherapy 177 Lu-DOTATATE SPECT SUV tumor-to-normal organ ratios (liver, spleen, and kidneys) in 24 patients at 4 and 24 h after cycle 1. These studies provide evidence of the potential usefulness of pretherapeutic scans for predicting posttreatment doses or for establishing correlations between post-and pretreatment scans in patients undergoing treatment for NETs.…”
mentioning
confidence: 74%
See 3 more Smart Citations